Strategic Repositioning For Convection Business Case Study: AR Vendor - Anindita, Pratisara Satwika; Toha, Mohamad (The Indonesian Journal of Business Administration, 2013)
The study aims to determine suitable position and strategy in order to reach superiority in convection business based on the company strengths and weaknesses. A study conducted in late 2012 at AR Vendor, a home-based convection company which focus on the t-shirt screen printing service. In response to the issue of the below average profit margin, the company has to rethink their position and strategy in handling the convection business environment. While AR Vendor business may growth in accordance to the population and economy growth, AR Vendor has to aware about shifting from manual to digital screen printing technology. Moreover, AR Vendor also has to pay attention to the reseller-customer preference in doing backward integration. From its internal environment, it also known that AR Vendor still did not optimizing its marketing activity and employees performance. Alternative of strategies was gathered through Porterâ€™s generic competitive strategies, which cost-leadership strategy was chosen as the most suitable strategy by using QSPM. Through business model, customer segments that suitable with suggested strategy is them whom prioritize the quality, low price, punctuality, and customization. The cost leadership strategy also supported by business model that encourage the profit enhancement through economies of scale and cost efficiency.Â Keywords: strategic positioning, strategic management, QSPM, business model